Design of a parabolic patch antenna in band L, with double layer and air substrate, for weather satellite reception - Aguirre D. (2017)
This paper presents the design of a parabolic patch antenna. The reflector of primary focus has 120cm of diameter, the proposed feeder has double layer and air substrate between its layers. The upper and lower square layers are supported by non-conductive material. The experimental axial ratio obtained is 0.8dB at 1.7 GHz, phi=0deg. The gain obtained is 23.4dB, the reflection coefficient obtained in 1.7 GHz is -14dB. The antenna can be used to receive information from polar orbit weather satellites in L band, at 1.7 GHz. The antenna must be used with a rotor with synchronized movement in azimuth and elevation for the satellite tracking.